Circulating endothelial cells and progenitors as prognostic factors during autoimmune thrombotic thrombocytopenic purpura: results of a prospective multicenter French study. (22nd September 2014) - Widemann, A.; Pasero, C.; Arnaud, L.; Poullin, P.; Loundou, A. D.; Choukroun, G.; Sanderson, F.; Lacroix, R.; Sabatier, F.; Coppo, P.; Dignat‐George, F.; Kaplanski, G.; et al.
Summary Background Autoimmune thrombotic thrombocytopenic purpura (AI‐TTP) is characterized by an excess of circulating ultralarge von Willebrand factor (VWF) caused by anti‐ADAMTS‐13 autoantibodies. Animal studies, however, have shown that endothelial cell activation may also be an important trigger of AI‐TTP. Objectives To prospectively study circulating biomarkers of endothelial lesion and activation, such as circulating endothelial cells (CECs), soluble P‐selectin (sP‐selectin), or VWF, and of endothelial repair, such as circulating progenitor cells (CPCs) and endothelial progenitor cells (EPCs), in AI‐TTP, in relation to disease severity and prognosis. Results Twenty‐two patients were included in this study. CEC (P < 0.01), VWF (P < 0.05) and sP‐selectin (P < 0.01) levels were significantly increased during crisis, and returned to baseline levels during remission. Both CEC (P < 0.05) and sP‐selectin (P < 0.05) levels were significantly higher in patients who died or developed neurologic sequelae. CPC levels were substantially increased during the acute phase of the disease (P < 0.001), and returned to baseline levels during remission. Among CPCs, EPC levels were also increased during crisis (P < 0.05) and significantly decreased during remission. Patients who received < 16 plasma exchanges (PEs) had significantly higher EPC counts (P < 0.05) than those who needed more numerous PEs to obtain remission, suggesting that initial EPC counts may be associated with faster endothelial repair. Conclusion The profile of circulating endothelial markers shows massive endothelial activation and repair/remodeling during AI‐TTP, and suggests that CECs and EPCs may be promising prognostic biomarkers of the disease.